2017
DOI: 10.4155/bio-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drug and Soluble Target Tolerant Antidrug Antibody Assay for Therapeutic Antibodies Bearing The P329G Mutation

Abstract: Aim:Bridging immunoassays for detection of antidrug antibodies (ADAs) are typically susceptible to high concentrations of residual drug. Sensitive drug-tolerant assays are, therefore, needed. Materials & methods: An immune complex assay to detect ADAs against therapeutic antibodies bearing Pro329Gly mutation was established. The assay uses antibodies specific for the Pro329Gly mutation for capture and human soluble Fcγ receptor for detection. Results: When compared with a bridging assay, the new assay showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It is recommended in cases where drug tolerance is poor resulting in ADA assays with significant drug interference, the sponsor should provide the totality of the data and demonstrate a good faith effort to develop a drugtolerant assay by considering exploring acid dissociation, acid-capture-elution (ACE), solid-phase extraction with acid dissociation (SPEAD), precipitation and acid method (PANDA) [33] or an alternative assay format [34,35]. However, if acid dissociation is used, there is a risk of denaturing ADA due to pH treatment, or the potential to release the soluble target from the therapeutic:target complex [36].…”
Section: Drug Tolerancementioning
confidence: 99%
“…It is recommended in cases where drug tolerance is poor resulting in ADA assays with significant drug interference, the sponsor should provide the totality of the data and demonstrate a good faith effort to develop a drugtolerant assay by considering exploring acid dissociation, acid-capture-elution (ACE), solid-phase extraction with acid dissociation (SPEAD), precipitation and acid method (PANDA) [33] or an alternative assay format [34,35]. However, if acid dissociation is used, there is a risk of denaturing ADA due to pH treatment, or the potential to release the soluble target from the therapeutic:target complex [36].…”
Section: Drug Tolerancementioning
confidence: 99%
“…Consequently, we developed a phycoerythrin (PE) coupled anti‐P329GLALA detection antibody (clone M‐1.7.24; “anti‐PGLALA‐PE”). This clone was previously shown to be highly specific for the IgG 1 ‐P329GLALA antibody format in a soluble assay system [ 18 ], but had not been tested in a cell‐based assay by flow cytometry. Using anti‐PGLALA, we showed that RG7769 bound to activated T cells expressing PD‐1 and TIM3, but not activated natural killer (NK) cells which exclusively expressed TIM3 (Figure S1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that in many tumors, upon anti‐PD‐1 therapy, other negative regulators of T cell activation can be co‐expressed, including T cell immunoglobulin and mucin domain‐containing protein 3 (TIM3) [ 16 , 17 ]. More recently, in order to simultaneously target PD‐1 and TIM3 in cancer patients, Roche developed RG7769 (also termed RO7121661), a bi‐specific mAb with an Fc gamma receptor silent IgG 1 P329GLALA backbone [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. RG7769 was designed so that its anti‐PD‐1 affinity is higher than its anti‐TIM3 affinity in order to avoid the antibody from binding to non‐T cells [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mixture was added to the TIC-Bi coated SA-MTP and incubated for 1 h. After incubation, the washing step was repeated. A human Fc R1 (CD64), #MAB1257 from R&D Systems Inc. (MN, USA) was digoxygenin (Dig) labeled and used as described by Wessels et al [21] as first detection reagent. This Fc R1, which binds IgG1, IgG3 and IgG4, was chosen to detect as many IgG subtypes as possible.…”
Section: Igg Aiamentioning
confidence: 99%